RETRACTED: Hydraulic model of digitalization of water accounting under the sluice gate - Arifjanov Aybek; Tadjiboyev Suhrob; Vokhidova Umida; Juraboyev Ismoil (E3S Web of Conferences, 2024)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001